1993
DOI: 10.1002/ajh.2830430204
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation system activation and increase of D‐dimer levels in peripheral arterial occlusive disease

Abstract: The aim of the present study was to document coagulation system activation and basal fibrinolysis in peripheral arterial occlusive disease (PAOD) at stage II of Fontaine's classification. In 34 patients, prothrombin fragment (F1 + 2), thrombin-antithrombin III complexes (TAT), and D-dimer concentrations were evaluated before and after a standard treadmill test. Basal levels in PAOD of F1 + 2 (1.25 +/- 0.19 nmol/liter) and of TAT (3.34 +/- 0.35 micrograms/liter) were significantly increased compared to those ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…12 In most studies, baseline D-dimer levels are reported to be higher in claudicants compared to healthy controls. 2,16,19,20 D-dimer levels significantly increase after exercise compared to the respective levels of healthy controls, 2,16,19,20 and it appears to persist up to 1 h postexercise. 2 This increase is not significant when compared to the baseline values.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…12 In most studies, baseline D-dimer levels are reported to be higher in claudicants compared to healthy controls. 2,16,19,20 D-dimer levels significantly increase after exercise compared to the respective levels of healthy controls, 2,16,19,20 and it appears to persist up to 1 h postexercise. 2 This increase is not significant when compared to the baseline values.…”
Section: Discussionmentioning
confidence: 92%
“…9 The other markers of coagulation activity, PF1 þ 2, are reported by two studies to be at a higher baseline level compared to controls and this difference between claudicants and healthy control persists in the early post-exertion period. 19,20 Only one study did not report any difference between the PF1 þ 2 pre-exertion levels of claudicants and smoking controls, but a significant increase was reported when compared to non-smoking controls. 11 Constans et al take a different approach and compares the immediate post-exertion and the post-resting levels of PF1 þ 2 to the respective baseline, reporting that immediately after exercise there is no significant increase to baseline, but after a period of rest PF1 þ 2 levels rise significantly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies published in 1993 addressed markers of thrombin in patients with PAD, showing a positive association between TAT and PAD65 and elevations of both F1.2 and TAT in patients with PAD, however, not related to severity of atherosclerosis 66. Heinrich et al and van der Bom and colleagues did not find significant associations of F1.2,67 or F1.2 or TAT38 with prevalent PAD, respectively.…”
Section: Literature Studiesmentioning
confidence: 96%